OPTIMALISASI KUALITAS KERJA DALAM MEMBERIKAN PELAYANAN PT. ANGKASA PURA 1 PERSERO BALI - Maria Febriend Syukur; I Wayan Sukadana (Jurnal Borneo Saintek, 2022)
This study aims to find out what strategies are carried out by the General service division at PT. Angkasa Pura I Persero in managing the company. In this case the General Service is responsible for managing various matters related to the company's operational activities. General service plays an important role in ensuring that every company activity can run well. For this reason, in order to facilitate roles and responsibilities, General Service must make a quality work strategy. Some of these important strategies are strategies for maintaining and being responsible for company assets, strategies for making RAB, and social strategies with external parties. With this strategy, General Service was able to make PT. Angkasa Pura I Persero Bali Survive until now. The above strategy ensures that the work and services of the General Service division are of high quality.